1996
DOI: 10.1111/j.1365-2648.1996.tb02940.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating attitudes to research in primary health care teams

Abstract: Despite top-down professional body and government agency pressure to increase the research base of clinical practice, there remains a considerable body of evidence which suggests that many ineffective, and even dangerous, health care interventions continue to be practised in areas where there are significant contradictory findings. While numerous explanations have been put forward which implicate the role of structural, organizational and informational barriers to integrating research with practice, less atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 14 publications
1
22
1
3
Order By: Relevance
“… 26 In a study of primary care teams, Hicks et al found that despite statements to the contrary, nurses saw research as peripheral to their jobs and unimportant. 27 In a similar vein, McSherry found minimal understanding of research among 300 nurses surveyed. 28 Other research highlights the constraints of lack of autonomy in practice, particularly when final decisions about care are taken by others, possibly not even in the profession.…”
Section: What Are the Problems?mentioning
confidence: 99%
“… 26 In a study of primary care teams, Hicks et al found that despite statements to the contrary, nurses saw research as peripheral to their jobs and unimportant. 27 In a similar vein, McSherry found minimal understanding of research among 300 nurses surveyed. 28 Other research highlights the constraints of lack of autonomy in practice, particularly when final decisions about care are taken by others, possibly not even in the profession.…”
Section: What Are the Problems?mentioning
confidence: 99%
“…Authors such as Champion & Leach [11], Hicks et al . [12] and Kuuppelomäki & Tuomi [13] state that a favourable attitude is highly correlated with the use of research, compared to other factors such as the competence to apply research results and the support of colleagues. The lack of motivation, interest, safety, as well as personal beliefs about the value of research, makes it difficult for its use in clinical nursing practice.…”
Section: Introductionmentioning
confidence: 99%
“…I internationella studier har attityder till forskning kartlagts bl.a. inom primärhälsovården (12,13,14). Forskningarna visar att majoriteten av primärhälsovårdens representanter ser forskningsresultat som oviktiga och perifera.…”
Section: Forskningsläget Om Evidensbaserad Vårdunclassified